2008
DOI: 10.1590/s0044-59672008000300010
|View full text |Cite
|
Sign up to set email alerts
|

Geographic pattern of genetic diversity in natural populations of Rosewood (Aniba rosaeodora), in the Central Amazonia

Abstract: Rosewood (Aniba rosaeodora Ducke, lauraceae) is an amazonian evergreen tree and a source of the purest linalool, the main component of its essential oil, which is very valuable in the international perfumery market. after decades of over-exploitation it is currently considered as threatened. We evaluated the genetic diversity and its distribution in four populations in Central amazonia. thirty-five reliable RaPD markers were generated, of which 32 were polymorphic (91.4%). variation was higher within the popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…In the current study planted Rosewood trees had a high seed removal rate, promoted by seed dispersal agents, and in native population a very high gene flow among the subgroups . This also corroborates to high RAPD diversity in natural adults populations of Rosewood (Santos et al, 2008), as well high polymorphism identified in Rosewood´s microsatellites locis (Angrizani et al, 2008). These results imply that seed removals might play an important role in gene movement in native Rosewood population, but we were unable to assess its total contribution since rates of gene flow via pollen flow were not evaluated.…”
Section: Spatial Distribution Gene Flow and Genetic Diversity Of Sapsupporting
confidence: 73%
See 1 more Smart Citation
“…In the current study planted Rosewood trees had a high seed removal rate, promoted by seed dispersal agents, and in native population a very high gene flow among the subgroups . This also corroborates to high RAPD diversity in natural adults populations of Rosewood (Santos et al, 2008), as well high polymorphism identified in Rosewood´s microsatellites locis (Angrizani et al, 2008). These results imply that seed removals might play an important role in gene movement in native Rosewood population, but we were unable to assess its total contribution since rates of gene flow via pollen flow were not evaluated.…”
Section: Spatial Distribution Gene Flow and Genetic Diversity Of Sapsupporting
confidence: 73%
“…As a result, its population has decreased to the point where the species is at risk of extinction (IBAMA, 1992). Nonetheless, high RAPD diversity in exploited natural populations of Rosewood was showed recently by Santos et al (2008). Has the low population densities of Rosewood in exploited forests have resulted in reduced seed set?…”
Section: Introductionmentioning
confidence: 99%
“…These studies are keys to developing strategies for conservation genetics of the remaining populations of endangered species. Genetics studies based on genetic markers, such as microsatellite markers, can help to illuminate such ecological and genetic processes in plant populations (Burczyk et al, 2004;Ashley, 2010). To assess these ecological and genetic processes using genetic markers, samples from adults, open-pollinated seeds, and/or regenerants (seedlings and juveniles) of the focus species must be used along with techniques such as parentage analysis (Burczyk et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Genetics studies based on genetic markers, such as microsatellite markers, can help to illuminate such ecological and genetic processes in plant populations (Burczyk et al, 2004;Ashley, 2010). To assess these ecological and genetic processes using genetic markers, samples from adults, open-pollinated seeds, and/or regenerants (seedlings and juveniles) of the focus species must be used along with techniques such as parentage analysis (Burczyk et al, 2004). Paternity analysis based on open-pollinated seeds enables the investigation of effective pollen flow and dispersal patterns, while maternity and paternity analysis based on regenerants enables the investigation of realized pollen and seed flow and dispersal patterns (Burczyk et al, 2004;Ashley, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation